Dipolar S=O center dot center dot center dot C=O and C-H center dot center dot center dot O interactions in the molecular organization of 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthoesters - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C-Crystal Structure Communications, 2009)
In the absence of conventional hydrogen bonding, the molecules of 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthoformate, C(18)H(20)O(10)S, (I), and 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthobenzoate, C(24)H(24)O(10)S, (II), are associated via C-H center dot center dot center dot O interactions. Molecules of (II) are additionally linked via dipolar S=O center dot center dot center dot C=O contacts. It is interesting to note that the sulfonyl O atom involved in the dipolar S=O center dot center dot center dot C=O contacts does not take part in any other interaction, indicating the competitive nature of this contact relative to the weak hydrogen-bonding interactions.